Shotgun metagenomics analysis of gut microbiota of three indigenous fish species from the Kizil River, Xinjiang - Yang, Jingru; Qiang, Zhuang; Zhang, Dandan; Hao, Huimin; Wei, Jie; Maira, Hamid Syeda; Wang, Weimin; Nie, Zhulan (Frontiers in Microbiology, 2025)
This study investigates the gut microbiota composition and functional adaptations in three indigenous fish species from the Kizil River, Xinjiang: Schizothorax biddulphi (SB), Diptychus maculatus (DM), and Triplophysa yarkandensis (TY), recognizing their ecological significance and the need for conservation insights. Shotgun metagenomics was employed to profile the gut microbiota and functional potential. Taxonomic and functional annotations were analyzed, including identification of dominant taxa, biomarkers (LEfSe), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways for metabolic functions, and Carbohydrate-Active enZymes (CAZy) database annotations. Environmental parameters (crude oil pollution, nitrogen levels, pathogen presence) were assessed, and dietary shifts during overwintering were characterized. Distinct gut microbiota profiles were identified: Proteobacteria, Acinetobacter, and Pseudomonas were dominant overall. Species-specific biomarkers were Micromonospora (DM); Proteobacteria, Firmicutes, Aeromonas, and Bacillus (SB); and Mucoromycota, Vibrio, and Alcanivorax (TY). DM and SB exhibited significantly higher Firmicutes/Bacteroidetes ratios and enhanced nutrient utilization capabilities compared to TY. Key functional pathways included enriched fructose/mannose metabolism (SB) and oxidative phosphorylation (DM). CAZy analysis revealed high CE3 abundance across species, with GT6/GT10 (SB) and PL22 (TY) serving as unique enzymatic biomarkers. Dietary shifts during overwintering occurred: DM and TY transitioned towards herbivory, while SB retained carnivorous tendencies despite increased plant consumption. All species showed reduced immunity, with DM and SB particularly vulnerable to Acinetobacter-related infections. Environmental analysis revealed crude oil pollution, elevated nitrogen levels, and contamination with A. baumannii. TY demonstrated notable salinity adaptability but heightened sensitivity to pollution. Host phylogeny exerted a strong influence on microbiota composition and metabolic functions. The results demonstrate host-specific microbial adaptation driven by phylogeny. The distinct functional profiles (nutrient utilization, key metabolic pathways like fructose/mannose metabolism and oxidative phosphorylation, CAZy enzymes) reflect ecological niche specialization. The observed dietary shifts and reduced winter immunity, compounded by environmental stressors (crude oil, nitrogen, A. baumannii), highlight critical vulnerabilities, especially for DM and SB. TY’s salinity adaptation is counterbalanced by pollution sensitivity. This study provides essential insights for developing targeted conservation strategies and sustainable aquaculture practices for these indigenous species within their natural habitat, emphasizing the need for pollution mitigation.